The influence of Memory Challenge Game Method and Students ‘Reading Speed towards Their Vocabulary Achievement at Grade VIII of SMP Negeri 19 Ambon - Threesje R Souisa; Emily F Aipassa (JURNAL TAHURI, 2019)
Vocabulary is commonly defined as all the words known and used by a particular person. Unfortunately, in learning process the students have limited words or vocabulary that caused them slow in reading a text. So, in order to increase students’ vocabulary this research was aimed at finding out the positive and significance influence of Memory Challenge Game Method and Reading Speed towards students ‘vocabulary. Quasi Experimental was used to conduct the study with pre-test and post-test non-equivalent control group design. The students from two classes namely class VIII7 as the Experimental group and class VIII5 as the Control group consisted of thirty students for each group. Descriptive and inferential statistics were applied in analyzing the data. The results revealed that the students’ vocabulary had significant increase by using Memory Challenge Game than using Bingo Game Method. It was showed on the mean score of Post Test of Experimental class higher than post-test of Control Class and the Ttest = 37.0. The result of reading speed rates of students in Experimental Class was higher than in Control Class. The result of the Ttest of both Memory Challenge Game Method and Reading Speed was 4.22 while for both Bingo Game Method and Reading Speed was 1.15. From these findings, it can be concluded that first, there was a positive and significance influence of the memory challenge game towards the student’ vocabulary achievement. Second, there was a positive and significance influence between the students’ reading speed and their vocabulary achievement. Third, there was a positive and significance influence of the memory challenge game method, and reading speed towards the students’ vocabulary achievement.